2007
DOI: 10.1021/jm070204r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and In Vivo Studies of Cu(II)-64-Labeled Cross-Bridged Tetraazamacrocycle-amide Complexes as Models of Peptide Conjugate Imaging Agents

Abstract: Copper-64, a positron emitter suitable for positron emission tomography (PET), demonstrates improved in vivo clearance when chelated by the cross-bridged tetraazamacrocycle CB-TE2A compared to TETA. Good in vivo clearance was also observed for 64Cu-CB-TE2A conjugated to a peptide, which converts one coordinating carboxylate pendant arm to an amide. To better understand the in vivo stability of peptide- conjugated CB-TE2A, cross-bridged monoamides were synthesized. Crystal structures of natCu(II)-CB-TEAMA and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 29 publications
1
87
0
Order By: Relevance
“…However, according to the reported results of the Cu-CB-TE2A (Cu (II) complex of the cross-bridged TE2A) [33], which has two trans-disubstituted carboxylate groups just like TE2A, there is very little change in the core coordination geometry around the Cu(II) ions, when one carboxylate group (carboxymethyl) of CB-TE2A was converted to an amide group (acetamido). In the X-ray crystallographic studies of CU(II)-CB-TEAMA, the amide pendant arm was found to be coordinated via the carbonyl oxygen and the distorted octahedral coordination geometry is maintained, as in the Cu-CB-TE2A complex [34]. The biodistribution studies also showed the good in vivo stability of the 64 Cu-crossbridged monoamides, supporting the hypothesis that CB-TE2A is able to be used as a BFC without any structural modifications of the macrocycle backbone [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the reported results of the Cu-CB-TE2A (Cu (II) complex of the cross-bridged TE2A) [33], which has two trans-disubstituted carboxylate groups just like TE2A, there is very little change in the core coordination geometry around the Cu(II) ions, when one carboxylate group (carboxymethyl) of CB-TE2A was converted to an amide group (acetamido). In the X-ray crystallographic studies of CU(II)-CB-TEAMA, the amide pendant arm was found to be coordinated via the carbonyl oxygen and the distorted octahedral coordination geometry is maintained, as in the Cu-CB-TE2A complex [34]. The biodistribution studies also showed the good in vivo stability of the 64 Cu-crossbridged monoamides, supporting the hypothesis that CB-TE2A is able to be used as a BFC without any structural modifications of the macrocycle backbone [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hexaazamacrobicyclic cage-type ligands, based upon the sepulchrate or sarcophagine cage motifs, have been efficiently radiolabeled under mild conditions and have been shown to possess high in vivo stability ( Figure 1). 4,20,21 However, the yield of antibody conjugation with these chelators is often low because of side reactions including protein cross-linking caused by the use of 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC). 22 Moreover, copper complexes of these ligands carry a net positive charge, which leads to high hepatic uptake and slow kidney clearance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 Moreover, copper complexes of these ligands carry a net positive charge, which leads to high hepatic uptake and slow kidney clearance. 23−25 Derivatives of 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) 26,27 and cross-bridged 4,11-bis-(carboxymethyl)-1,4,8,11-tetraaza-bicyclo[6.6.2]hexadecane (CB-TE2A) 19,20 form negative or neutral complexes with Cu(II) and demonstrate high in vivo stability ( Figure 1). In fact, the latter forms one of the most stable complexes with 64 Cu(II) 28 and the Cu(II)-CB-TE2A complex is more resistant to the reductive metal loss than any other known tetramacrocyclic complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…28 Cross-bridged monoamides, model compounds of peptide-conjugated ECB-TE2A, showed high in vivo stability and fast body clearance. 29 On the basis of high structural similarity between ECB-TE2A and DM-TE2A, high in vivo stability of 64 Cu-radiolabeled DM-TE2A-bioconjugate is also expected. However, all further conjugation using MM/ DM-TE2A and following in vivo stability of conjugates should be evaluated by appropriate experiments.…”
mentioning
confidence: 99%